Biosynthesis of Trehangelin in Polymorphospora rubra K07–0510: Identification of Metabolic Pathway to Angelyl‐CoA. (17th June 2016) - Inahashi, Yuki; Shiraishi, Taro; Palm, Kaia; Takahashi, Yoko; Ōmura, Satoshi; Kuzuyama, Tomohisa; Nakashima, Takuji
Abstract: Trehangelins are trehalose angelates discovered from endophytic actinomycete Polymorphospora rubra K07‐0510. We identified the trehangelin biosynthetic gene cluster, including genes that encode a glycoside hydrolase‐like protein ( thgC ), α‐amylase ( thgD ), 3‐ketoacyl‐ACP synthase III ( thgI ), 3‐ketoacyl‐ACP reductase ( thgK ), enoyl‐CoA hydratase ( thgH ) and acyl transferase ( thgJ ). Heterologous expression of thgH, thgI, thgJ and thgK confirmed the importance of these genes in the biosynthesis of trehangelin A. Enzymatic activity studies showed that ThgI catalyses the condensation of acetyl‐CoA and methylmalonyl‐CoA to 2‐methylacetoacetyl‐CoA (MAA‐CoA), ThgK catalyses NADPH‐dependent reduction of MAA‐CoA to 3‐hydroxy‐2‐methylbutyryl‐CoA (HMB‐CoA) and ThgH catalyses the dehydration of HMB‐CoA to angelyl‐CoA (AN‐CoA). This is the first report on the elucidation of the enzymatic formation of AN‐CoA. Abstract : We identified the biosynthetic gene cluster of trehangelin in Polymorphospora rubra K07‐0510 by heterologous expression of the genes thgH, thgI, thgJ and thgK . The enzymatic assays of ThgI, ThgK and ThgH confirmed the role of these proteins in biosynthesis of angelyl‐CoA from acetyl‐CoA and methylmalonyl‐CoA.